CMET-14. DISTANT BRAIN FAILURE FOLLOWING STEREOTACTIC RADIOSURGERY FOR BRAIN METASTASES FROM NON-SMALL CELL LUNG CANCER. (5th November 2018) - Keller, Andrew; All, Sean; Patel, Hanisha; Nguyen, Steven; Pearson, Luke; Ramakrishna, Naren
Abstract: PURPOSE: We examined distant brain failure rates and underlying prognostic factors among patients treated with SRS for brain metastases from NSCLC. METHODS: We performed an IRB-approved retrospective study of 178 NSCLC patients treated with Linear Accelerator-based stereotactic radiosurgery (SRS) for 526 brain metastases. Median time to distant brain failure (DBF) was defined as time from initial SRS to MRI revealing a new lesion. Kaplan Meier and Cox proportional hazards model were used for statistical evaluation. All but 10 patients were classified by histology, with the majority (76%) classified as adenocarcinoma. 116 patients (65%) had uncontrolled extracranial disease. 22 patients (12%) received previous WBRT and 15 patients (8%) received concurrent WBRT. 6 patients were ALK positive and 63 were ALK-negative. 26 patients were EGFR positive and 64 were EGFR negative. RESULTS: The median time to development of 1 brain metastasis was 8 months, with 22 patients (12%) only developing 1 additional brain metastasis and 89 patients (50%) developing greater than 1 additional brain metastasis. Median time to development of 2–4 brain metastases was 12 months, with 39 patients (22%) developing only 2–4 additional brain metastases and 50 patients (28%) developing greater than 4 additional brain metastases. Median time to development of greater than 4 additional brain metastases was 26 months. Median time to leptomeningeal disease (LMD) was 62 months, with 21 patients (12%) developing LMD. On univariate analysis, adenocarcinoma histology (p=0.031), EGFR mutation negative or unknown (p=0.042), and controlled extracranial disease (p=0.011) were positive prognostic factors for time to development of 1 additional brain metastasis. CONCLUSION: We report the incidence of distant brain failure among lung cancer patients treated with SRS. Our study revealed that the probability of distant brain failure is increased for those with EGFR mutation, active extracranial disease, or non-adenocarcinoma histology.